Hepatobiliary and Pancreatic Cancer (Cancer Dissemination Pathways, 2018)
This book describes the pathways of dissemination of primary liver, biliary, and pancreatic neoplasms and proposes a practical and clinically driven approach to their imaging. The typical dissemination pathways for hepatocellular carcinoma, cholangiocarcinoma, exocrine pancreatic carcinoma, and neuroendocrine pancreatic tumors are systematically reviewed, and more unusual pathways are also documented. The content is presented in an extremely schematic way, with numerous high-quality graphical illustrations and multimodality images (US, CT, MRI, and PET) that are accompanied by clear explanatory text. The clinical significance of findings and potential therapeutic options are explained whenever appropriate. In addition, relevant background information is provided on the role of morphopathological drivers of cancer spread and anatomy.